Pengaruh Kepedulian Orang Tua Terhadap Perkembangan Kognitif Anak Berdasarkan Analisis Pola Pengasuhan - Rosi Rosyani; Heri Yusuf Muslihin; Taopik Rahman (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2022)
Early childhood development needs to be considered properly, especially cognitive development. However, there are still many parents who are less sensitive to this. Therefore, the authors conducted a study to determine the level of parental concern for the cognitive development of children who were analyzed based on parenting patterns. The research method used a survey method with a sample of 20 parents and 20 teenagers. The results show that there are 45% of parents who choose authoritative parenting and 45% of adolescents who get authoritative parenting from their parents. With this figure, parenting is very influential on children's cognitive development, some of the effects are 50% of people are easy to interact socially, 75% of people are easy to catch life's problems, 55% of people are difficult to find solutions to their problems, 60% are able to understand the concept of value/ love even though it is still difficult, and 65% feel a little involved in the learning process. The author advises readers to always apply authoritative parenting because it is included in the ideal parenting pattern. Keywords: parenting; cognitive development; early childhood References AlRasyid, H. (2018). Gaya Kepemimpinan Pada Hotel Best Western Surabaya. https://doi.org/10.31219/osf.io/rn69a Angga Saputra, A. S., & Lalu Suryandi, L. S. (2021). Perkembangan Kognitif Anak Usia Dini Dalam Perspektif Vygotsky Dan Implikasinya Dalam Pembelajaran. PELANGI: Jurnal Pemikiran dan Penelitian Islam Anak Usia Dini, 2(2), 198–206. https://doi.org/10.52266/pelangi.v2i2.582 Anisah. (2011). Pola Asuh Orang Tua Dan Implikasinya Terhadap Pembentukan Karakter Anak. Jurnal Pendidikan Universitas Garut, 5(1), 70–84. Aslan, A. (2019). Peran Pola Asuh Orangtua di Era Digital. Jurnal Studia Insania, 7(1), 20. https://doi.org/10.18592/jsi.v7i1.2269 Chapnick, A. (2008). The golden age. International Journal, 64(1), 205–221. https://doi.org/10.1177/002070200906400118 Chusnandari, M. (2018). Hubungan Antara Pola Asuh Orangtua Dengan Perkembangan Kognitif Anak Usia Dini. Journal Of Early Childhood Islamic Education, 2(2), 209–230. Debitiya, I. (2020). Pengaruh Pola Asuh Terhadap Perkembangan Kognitif Anak Usia Dini di Desa Tanjung Medan Utara. 1601240013. Dialektika, J., & Pgsd, J. (2016). Kata kunci : konsep dasar, perkembangan kognitif, Jean Piaget. 5(1), 1–10. Diana, F. M. (2010). Pemantauan Perkembangan Anak Balita. Jurnal Kesehatan Masyarakat Andalas, 4(2), 116–129. Elida, P., & Remaja, P. P. (1991). Perkembangan Peserta Didik. In Dirjen Dikti: Jakarta. Fitriyani, L. (n.d.). Peran pola asuh orang tua dalam mengembangkan kecerdasan emosi anak. XVIII(1), 93–110. Hidayati, N. I. (2014). Pola Asuh Otoriter Orang Tua, Kecerdasan Emosi, dan Kemandirian Anak SD. Persona:Jurnal Psikologi Indonesia, 3(01). https://doi.org/10.30996/persona.v3i01.364 Imroatun, I. (2017). Media Belajar Bigbook Bagi Pengembangan Baca Nyaring Anak Usia Dini. Seminar Nasional Pembelajaran Baca, Tulis, Dan Hitung Tingkat Permulaan Bagi Anak Usia Dini, 119–127. Imroatun, I., Nirmala, I., Juhri, J., & Muqdamien, B. (2020). Kajian Literatur Pengasuhan Anak Usia Dini Dalam Islam. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 5(1), 57–66. Isti Pujihastuti. (2010). Isti Pujihastuti Abstract. 2(1), 43–56. Kristyowati, R., & Purwanto, A. (2019). Pembelajaran Literasi Sains Melalui Pemanfaatan Lingkungan. Scholaria: Jurnal Pendidikan dan Kebudayaan, 9(2), 183–191. https://doi.org/10.24246/j.js.2019.v9.i2.p183-191 Mu’min, S. A. (2013). Teori Pengembangan Kognitif Jian Piaget. Jurnal AL-Ta’dib, 6(1), 89–99. Nurhayati, R. (2019). Membangun Budaya Literasi Anak Usia Dini dalam Keluarga. Nuansa Akademik: Jurnal Pembangunan Masyarakat, 4(1), 79–88. https://doi.org/10.47200/JNAJPM.V4I1.918 Oktariani, O. (2021). Dampak Toxic Parents dalam Kesehatan Mental Anak. Jurnal Penelitian Pendidikan, Psikologi Dan Kesehatan (J-P3K), 2(3), 215–222. https://doi.org/10.51849/j-p3k.v2i3.107 Paud, D. I., & Magelang, K. (2017). = 0,439 Sedangkan R. 2, 565–579. Permasalahan, A. (n.d.). Analisis Permasalahan "Perkembangan Kognitif Anak Usia Dini ”. 2(1), 82–90. Pujianti, R., Sumardi, S., & Mulyadi, S. (2021). Perkembangan Sosial Emosional Anak Usia 5-6 Tahun Selama Pembelajaran Jarak Jauh Di Raudhatul Athfal. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 6(2), 117–126. https://doi.org/10.32678/AS-SIBYAN.V6I2.4919 Santoso, F. S. (2020). Lingkungan Keluarga Sebagai Awal Pengembangan Kewirausahaan Islam. Nuansa Akademik: Jurnal Pembangunan Masyarakat, 5(1), 13–22. https://doi.org/10.47200/jnajpm.v5i1.418 Sarjana, P., Guru, P., & Athfal, R. (n.d.). Tahapan perkembangan kognitif pada masa early childhood. I, 33–49. Sartini, E. (2016). Strategi Pembelajaran Pada Bidang Pengembangan Kognitif Dengan Menggunakan Benda. Tasikmalaya, U. M. (n.d.). Abstrak. 1(1), 1–12. Widyaningtyas, W., Shari, D., Saleh, N. R., & Asmara, B. (2021). Menigkatkan Kemampuan Kognitif Mengenal Bentuk Geometri Melalui Media Bahan Alam Batu Pelangi. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 6(1), 41–52. https://doi.org/10.32678/AS-SIBYAN.V6I1.2940 Zakiyah, N., Nurhikma, N., & Asiyah, A. (2021). Pola Asuh Orang Tua Dalam Membentuk Karakter Disiplin Anak Usia 5-6 Tahun Pada Masa Pandemi COVID-19. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 6(2), 127–138